Homeowner associations and sharing economy innovations: Empowering taxpayers while fostering citizen participation - Stephen K. Callaway (Cogent Business & Management, 2018)
This paper examines organizations that deliver “club goods,” which demonstrate aspects of both private and public goods. One such organization is the homeowner association (HOA), which has been termed “private government.” The HOA has a paradigm that may balance strengths of the private sector with those of the public sector. Yet if the dominant paradigm of the HOA were to be redefined, there may be a potential source of innovation proving beneficial to society, a research focus termed social innovation. Further, technology and lessons from the sharing economy may be pertinent to this redefinition of HOAs. The sharing economy, and the dissemination of club goods, by blurring the distinction between provider and consumer, may be an understudied way to promote innovation in society. A statistical analysis of HOAs in the United States was undertaken, and using SPSS, simple linear regression demonstrated that HOA amenities and elementary schools significantly affect neighborhood desirability, measured by home sales prices. Finally, based on the theoretical and empirical contributions of this study, a brief proposal on how to revamp HOAs is described.
Keywords: 650